2007
DOI: 10.1007/bf03022655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term postoperative celecoxib administration on patient outcome after outpatient laparoscopic surgery

Abstract: Short-term administration of celecoxib, 400 mg x day(-1) po, decreased postoperative pain and the need for opioid-containing analgesic medication, leading to an improved quality of recovery after outpatient laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
3
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 33 publications
(44 reference statements)
1
41
3
3
Order By: Relevance
“…These authors have further suggested that elimination of opioid-based analgesia would be highly desirable in the future. These important findings have been recently confirmed by White et al 14 In our prospective study involving the administration of celecoxib on the day of surgery and the subsequent three days after outpatient laparoscopic surgery as part of a multimodal analgesic regimen, we found that these patients not only experienced less pain and reduced need for opioid-containing oral analgesics, but more importantly, patients were able to resume normal activities of daily living one-to-two days earlier.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…These authors have further suggested that elimination of opioid-based analgesia would be highly desirable in the future. These important findings have been recently confirmed by White et al 14 In our prospective study involving the administration of celecoxib on the day of surgery and the subsequent three days after outpatient laparoscopic surgery as part of a multimodal analgesic regimen, we found that these patients not only experienced less pain and reduced need for opioid-containing oral analgesics, but more importantly, patients were able to resume normal activities of daily living one-to-two days earlier.…”
supporting
confidence: 85%
“…12,13 These benefits have been confirmed in more recent studies, 14,15 and multimodal techniques are the currently recommended practice in fast-track clinical care plans. 5 It is clear that the reliance on a single non-opioid analgesic modality [e.g., local analgesics, non-steroidal anti-inflammatory drugs (NSAIDs) and/or acetaminophen] will not suffice to control moderate-severe postoperative pain, and excessive reliance on opioid analgesics produces too many undesirable side effects.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…35 Historically, factors with a direct impact on discharge readiness and institutional cost were assessednausea and vomiting, severe pain, 36-39 psychological distress, 37,38,[40][41][42] and basic physiological function. [43][44][45] With the advent of patient-centred care, recovery has developed into a multidimensional construct, with recovery assessment tools addressing physical (nociceptive), [36][37][38][39] psychological (emotive, satisfaction), 37,38,[40][41][42] functional (ADLs), [36][37][38][39][40][41][42]46 and more recently, cognitive domains. The latter has become more pertinent in the advent of an aging population and increasing awareness of the interplay between the perioperative inflammatory state, anesthetic agents, and neurodegenerative processes.…”
Section: Measurement Of Recoverymentioning
confidence: 99%